Pengembangan Media Kotak Pintar Berbasis Teknologi Qr Code untuk Meningkatkan Kemampuan Literasi Numerik Anak Usia Dini - Resa Tifeni Az-Zahra; Dadan Suryana; Yaswinda; Delfi Eliza (Jurnal Penelitian Pendidikan IPA, 2025)
Children's numerical literacy skills have not developed optimally. This can be seen in learning, where although children can mention numbers 1 to 20, they still have difficulty recognizing number symbols and matching the number with the number symbol. This condition is caused by the lack of use of technology-based learning media specifically designed for children. This research aims to develop QR Code-based smart box media to improve early childhood numerical literacy skills. This research method uses the Research and Development model from Borg and Gall. Validation was carried out by 3 experts, the test subjects were Pertiwi 1 Padang kindergarten students. Data collection techniques using interviews, questionnaires, and observation sheets. Data analysis was carried out validity analysis, practicality analysis, and effectiveness test analysis using SPSS V. 25. Based on the results of the analysis, the QR Code-based smart box media has 96% instrument validation test results, 90% media validation test and 92% material validation test with very valid eligibility criteria. Based on the calculation of the N-Gain test results of 0.52, meaning that the development of QR Code-based smart box media to improve early childhood numerical literacy skills is in the medium category. Furthermore, a paired sample t-test was conducted with the results of sig. (2-tailed) of 0.000 <0.05 with α = 0.05 which means that there is a difference in the average value between the pretest and posttest scores of numerical literacy skills in early childhood. It can be concluded that the development of QR Code-based smart box media is effective for significantly improving the numerical literacy skills of early childhood in kindergarten.